Analysis of the Development of the Credit Derivative Market - Stateva, Yordanka (Research Papers, 2005)
The intensive development of credit derivatives market has motivated a lot of research on financial instruments for credit risk management. The financial products on credit risk are becoming more and more popular due to different reasons. The main reason is that the global financial market nowadays contains much larger exposure to credit risk than to interest rate- or exchange rate risk. The credit risk is the main component of a great part of bank activities.The credit derivatives market is a market where credit risk, respectively credit protection is purchased and sold.The credit derivatives represent a new generation of derivative products – this is the last financial innovation since the beginning of 90s of 20th century.The main kinds of credit derivatives have been analyzed: 1. Credit Default Swap. 2. Total Return Swap. 3. Credit-Linked Notes. 4. Financial Products on credit spread: 4.1. Credit Spread Forward. 4.2. Credit Spread Option. 4.3. Credit Spread Swap.The credit derivatives market is still only over-the-counter. There are preparations going on for introducing a futures contract on a credit index. This will create an exchange sector of the credit derivatives market